Gender Disparities in Cambodian Higher Education (2015 – 2020): A Mixed-Methods Analysis of Enrollment, Performance, and Policy - Mach Suon (MASI Mandiri Edukasi, 2025)
This study examines gender disparities in Cambodian higher education from 2015 to 2020, focusing on both enrollment patterns and academic performance across degree levels. The research aims to assess the effectiveness of national policies in promoting gender equity and to identify structural barriers limiting female participation, especially at graduate levels. A mixed-methods approach was employed, combining qualitative policy analysis with quantitative statistical techniques, including descriptive statistics and independent sample t-tests. Data were sourced from official reports issued by the Ministry of Education, Youth and Sport, and international organizations such as UNESCO and the World Bank. Findings reveal that while gender parity has been nearly achieved at the associate and bachelor's levels, women remain significantly underrepresented in master's and PhD programs. T-test results show no significant performance differences at undergraduate levels, but statistically significant disparities favoring male students were observed at graduate levels. Despite the implementation of gender-focused policies, systemic barriers, including financial constraints and lack of institutional support, continue to affect women’s access to advanced education. This study fills a critical gap in the literature by offering a longitudinal and policy-informed perspective on gender equity in Cambodian higher education.